ANALYSIS OF THE CAUSES OF SHIP ACCIDENTS WHILE NAVIGATING IN AREAS WHERE THERE ARE RESTRICTIONS IN THE SHIP’S AIR DRAFT - Бичковський, Ю.В. (SWorldJournal, 2025)
повітряна осадка судна і шляхи її розрахунків.